IMPLEMENTASI MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUALIZATION, AND INTELLECTUALY BERBANTUAN ALAT PERAGA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - M. Nuur'aini Sholihat (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
This research is motivated by the low mathematical problem solving ability of students in class VIII MTs Al-Mubarok due to the lack of application of learning models. This study aims to determine the improvement of students' mathematical problem solving abilities who obtained the SAVI learning model with the help of teaching aids better than those using conventional learning models. The method that will be used in this research is quasi-experimental. The population of this study were students of MTs Al Mubarok while the samples were class VIII A and class VIII B. The material given was statistics. The results showed that  so that the increase in mathematical problem solving abilities of students who learned to use the SAVI model with the help of teaching aids was better than students who learned to use conventional models.